Beta-lactamase inhibition activity screening of methanolic and ethanolic extracts of selected Philippine plants - Balutoc, Iris Patrisha Abigail C.; Calimon, Vanna Melinda S.; Magno, Daryl E. (2017)
The discovery of antibiotics resulted to a therapeutic revolution which gave cure to lethal infectious diseases and disabled infections. However, the emergence of resistance to β-Lactam antibiotics rendered the most widely produced and used antibacterial drugs in the world useless. This study generally aims to evaluate the β-lactamase inhibition activity of selected Philippine plant samples. The β-lactamase inhibitory action of methanolic or ethanolic extracts of fifty plant samples were quantified through nitrocefin competition assay. The extracts of Durio zibethinus, Voacanga globosa, Moringa oleifera, and Melanolepis multiglandulosa showed 70.05%, 80.18%, 68.39%, and 52.97%, respectively. Thin-layer chromatography and phytochemical constituent testing were done to characterize the extracts. The methods, however, did not yield conclusive results which can be attributed to the low concentration of phytochemical constituents present in the extract. Since the susceptibility and synergistic effects of the four plant samples was not determined, the four samples can be tested to clinical isolates to determine its activity against microorganism with beta-lactamase enzyme.